Tuning the photophysical properties of lanthanide(iii)/zinc(ii) 'encapsulated sandwich' metallacrowns emitting in the near-infrared range. Issue 10 (3rd February 2022) - Eliseeva, Svetlana V.; Nguyen, Tu N.; Kampf, Jeff W.; Trivedi, Evan R.; Pecoraro, Vincent L.; Petoud, Stéphane
Abstract : We have created a family of 'encapsulated sandwich' Zn16 Ln(HA)16 metallacrowns and by detailed quantitative analysis demonstrated how the nature of the hydroximate ligand impacts photophysical properties of these complexes. Abstract : A family of Zn16 Ln(HA)16 metallacrowns (MCs; Ln = Yb III, Er III, and Nd III ; HA = picoline- (picHA 2− ), pyrazine- (pyzHA 2− ), and quinaldine- (quinHA 2− ) hydroximates) with an 'encapsulated sandwich' structure possesses outstanding luminescence properties in the near-infrared (NIR) and suitability for cell imaging. Here, to decipher which parameters affect their functional and photophysical properties and how the nature of the hydroximate ligands can allow their fine tuning, we have completed this Zn16 Ln(HA)16 family by synthesizing MCs with two new ligands, naphthyridine- (napHA 2− ) and quinoxaline- (quinoHA 2− ) hydroximates. Zn16 Ln(napHA)16 and Zn16 Ln(quinoHA)16 exhibit absorption bands extended into the visible range and efficiently sensitize the NIR emissions of Yb III, Er III, and Nd III upon excitation up to 630 nm. The energies of the lowest singlet (S1 ), triplet (T1 ) and intra-ligand charge transfer (ILCT) states have been determined. Ln III -centered total ( Q LLn) and intrinsic ( Q LnLn) quantum yields, sensitization efficiencies ( η sens ), observed ( τ obs ) and radiative ( τ rad ) luminescence lifetimes have been recorded and analyzed in the solid state and in CH3 OH and CD3 OD solutions for all Zn16 Ln(HA)16 . We found that, within the Zn16 Ln(HA)16 family, τ rad values are not constant for a particular Ln III . The close in energy positions of T1 and ILCT states in Zn16 Ln(picHA)16 and Zn16 Ln(quinHA)16 are preferred for the sensitization of Ln III NIR emission and η sens values reach 100% for Nd III . Finally, the highest values of Q LLn are observed for Zn16 Ln(quinHA)16 in the solid state or in CD3 OD solutions. With these data at hand, we are now capable of creating MCs with desired properties suitable for NIR optical imaging.